Integrating Financial Sector Issues and FSAP Assessments into Surveillance : Progress Report. (Policy Papers; Policy Paper ;, 2009)
Improving the quality of the Fund's financial sector analysis and integrating it with surveillance is a major undertaking that involves action on several fronts. The 2007 Financial Sector Taskforce Report ('Taskforce Report') provided a comprehensive assessment of the status of financial sector analysis in the Fund and established a broad organizing framework on how to integrate better finance into Article IV surveillance. The 2008 Triennial Surveillance Review (TSR) and supplements developed this theme further, and the Board's ensuing Statement on Surveillance Priorities made the integration of macroeconomic and financial sector surveillance one of the four overarching operational priorities for Fund surveillance.